Myristicin Inhibit Invasion and Migration of Melanoma Cells through Suppression of MMP2 and MMP9 Gene Expression - Krisnayanti, Ni Putu Eka; Mariya, Silmi; Indriawati, Iin; Dayana, Hepy; Zaelani, Bella Fatima Dora; Tjandrawinata, Raymond R.; Darusman, Huda Shalahudin (Science and Technology Indonesia, 2024)
Melanoma is the deadliest type of skin cancer, having a high mortality rate. This cancer has an aggressive nature, is highly invasive, and has the tendency to metastasize. Matrix metalloproteinases (MMPs) are essential in that process, especially MMP2 and MMP9. Their expression is upregulated during metastasis progression. Myristicin is one example of a compound that can be utilized to target MMP 2 and MMP 9 in melanoma. This research concerns the activity of myristicin to inhibit melanoma cell invasion and migration by suppressing MMP2 and MMP9 gene expression. The MTT assay in this study demonstrated that myristicin exhibited strong cytotoxic activity against melanoma cells. This compound works in a dose-dependent manner by inhibiting cell migration and invasion. The invasion test was performed using the transwell assay, whereas the migration test was performed using the wound healing assay. The invasion assay results were consistent with MMP2 and MMP9 gene expression. These two genes were analyzed using the RT-qPCR technique. It has been demonstrated that low gene expression in melanoma cells inhibits cell invasion. In contrast, higher MMP2 and MMP9 gene expression was associated with an increase in the number of invasive cells on average. However, MMP2 and MMP9 in excessive expression and uncontrolled activity impair the ability of melanoma cells to form a monolayer sheet to cover wound gaps. This condition significantly reduced the migration rate and percentage of wound closure.